Exploration of contraceptive awareness and decision making among married women of reproductive age in semi urban area of Tamil Nadu - Saravanan, Sinduja; Maiya, Rakesh; Akram, R. M. Waseem; Jain, Timsi (International Journal Of Community Medicine And Public Health, 2019)
Background: India was the first country to have launched a National Program for Family Planning in 1952, but still there is no control on population growth. The objective was to assess the knowledge, attitude and practices of contraceptives among married women in semi urban area of Tamil Nadu. Methods: A community based cross sectional study was conducted in a semi urban area of Tamil Nadu. Married women of reproductive age (15-49) were included. Purposive sampling technique was used to select the subjects and self-administered questionnaire was used as study tool. Results: In this study about 91.80% were aware of at least one of the contraceptive methods but only 64.75% women used. The most common reason for using contraception was small family norms (75.89%) and for not using contraception was worried about side effects. The method commonly preferred was sterilisation (63.93%). The process of decision making was done mutually by both husband and wife (76.79%). There is an association existing between the education and awareness. Conclusions: On overall analysis it was found that only 49% are aware of contraception. Thus by proper motivation, counselling and improving facilities at both government and private sector, the unmet needs of contraception can be achieved.